Efektivitas Pengembangan Perangkat Pembelajaran Fisika SMA Berbasis Science Environment Technology and Social (SETS) - Deswita, Pipi; Firmansyah, Firmansyah (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2020)
The purpose of this study was to examine the effectiveness of Physics learning equipments based on the Science Environment Technology and Social Approach (SETS). Learning with the SETS approach is expected to encourage students to understand the concepts of physics well, which can be applied in everyday life. This research uses McKenny's model which consists of preliminary, prototyping stage, and assessment stage. To see the effectiveness of the learning device is done at the assessment stage. At the assessment stage, three assessments are carried out, namely, attitude assessment, knowledge assessment, and skills assessment. The attitude and skills assessment was carried out by two observers by completing the observation questionnaire. Knowledge assessment is done by giving physics questions that have been validated by experts to students. This assessment is carried out in stages and each meeting is held in class by the observer. The results of this study indicate that high school physics learning equipments based on Science Environment technology and Social are in the category of very effective so it is feasible to be applied in the learning process.